Robust feedback control of flow separation using plasma actuators - Pasquale, Laura (2017)
This thesis addresses the problem of controlling the unsteady flow separation over an aerofoil using plasma actuators, with the aim of improving the performance of fluid systems through the use of robust feedback controllers. Despite the complexity of the dynamics of interest, it is shown how the problem of controlling flow separation can be successfully formulated and solved as a simple output regulation problem.